Design and optimisation of compact RF energy harvesting device for smart applications. Issue 2 (1st January 2014) - Ajmal, T.; Dyo, V.; Allen, B.; Jazani, D.; Ivanov, I.
Abstract : An optimised design of a radio frequency energy harvesting antenna is presented. The antenna is based on a compact ferrite rod which, together with the electronics, can directly replace batteries in suitable applications. The antenna is optimised such that the energy available for the applications is maximised, while considering constraints such as the device geometry and the Q ‐factor. That the antenna can power a wireless sensor node is shown from the ambient medium wave transmissions.